Health literacy : new directions in research, theory and practice - Logan, Robert A.; Siegel, Elliot R. (Studies in health technology and informatics ;, 2017)
"New directions in health literacy research, theory, and practice' provides an introduction to health literacy research and practice and highlights similar scholarship in related disciplines. Although the book is intended primarily for health literacy researchers, practitioners and students, the editors suggest the book's diverse topics and approaches are of interest to health care and public health researchers, practitioners, and students in addition to scholars in related fields, such as health communication, science communication, consumer health informatics, library science, health disparities, and mass communication"